Quizzing Students about their Writing: Implications for Deterring and Detecting Contract Cheating, and Promoting Academic Integrity and Greater Engagement - Quesnel, Matthew; Guderian, Robert; Stoesz, Brenda (Canadian Perspectives on Academic Integrity, 2023)
Contract cheating is a significant concern in the higher education sector, and a multi-faceted approach focusing on student learning and growth, in addition to deterring and detection cheating, is necessary to address the issue. One way to support student learning is by encouraging active engagement in learning activities and assessments. To this end, we explored the utility Auth+ by Sikanai, an authorship verification platform that auto-generates six multiple-choice questions based on students’ writing submissions and generates scores based on responses to the questions. Auth+ is designed to encourage students to engage in the learning process and to facilitate the detection of potential contract cheating. Auth+ was implemented in a third-year computer science course, and 24 students shared their perceptions of its value for teaching and learning. Only 25% of students agreed that Auth+ would be useful in their studies but 62.5% agreed it would deter contract cheating. We also found an association between Auth+ scores and individual differences in working memory (τB = .391). Our findings suggest that, with further technology development, authorship verification platforms may be useful for promoting academic integrity and deeper engagement in learning at scale. Training educators to interpret the results and use them as part of a multi-faceted strategy for promoting academic integrity and reduce academic misconduct is important.